State Ownership, Legal Institution, and Independent Director Compensation: An Exploratory Study in China - Adithipyangkul, Pattarin; Leung, T. (Routledge, 2015)
This study examines the determinants of independent director compensation in China, with particular interest in the impact of state ownership and legal institutions. Controlling for the characteristics of directors, boards, and firms, we find independent director compensation is positively related to attributes of a director’s human and social capital such as education, effort, professional expertise, and connections (guanxi). We show that independent director pay is determined differently across ownership structures. Independent directors are paid less in companies owned by local government units, and independent directors in such companies are paid less in a region with more greatly developed legal institutions. This study contributes to the limited literature on independent director compensation by extending beyond the market economies to explore the determinants of independent director compensation in a transitional economy such as China. It also adds to the literature on legal institutions by examining the impact of legal development on compensation. Finally, this study informs the public of the current compensation practice, which will facilitate future policy making.